2016
DOI: 10.1093/molbev/msw092
|View full text |Cite
|
Sign up to set email alerts
|

The Nuanced Interplay of Intrinsic Disorder and Other Structural Properties Driving Protein Evolution

Abstract: Protein evolution often occurs at unequal rates in different sites along an amino acid chain. Site-specific evolutionary rates have been linked to several structural and functional properties of proteins. Previous analyses of this phenomenon have involved relatively small datasets and, in some cases, the interaction among multiple structural factors is not evaluated. Here, we present the results of a large-scale phylogenetic and statistical analysis, testing the effects and interactions of three structural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…The lack of three-dimensional constraint may explain the fast evolution of these protein regions. However, it has been shown that there are amino acid residues that maintain the intrinsic disorder and that these residues are under stronger evolutionary constraint than in ordered regions (Ahrens et al 2016). It is therefore important to note that the vast majority of IDP regions experienced substantial purifying selection during their evolution (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of three-dimensional constraint may explain the fast evolution of these protein regions. However, it has been shown that there are amino acid residues that maintain the intrinsic disorder and that these residues are under stronger evolutionary constraint than in ordered regions (Ahrens et al 2016). It is therefore important to note that the vast majority of IDP regions experienced substantial purifying selection during their evolution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, parts exposed to the solvent protein surface evolve much faster (Franzosa and Xia 2009). IDPs generally tend to evolve more rapidly, largely attributed to relaxed purifying selection due to the lack of structural constraint (Brown et al 2011), although Ahrens et al (2016) found that sites that were predicted to be disordered and to have secondary structure were evolving at a lower rate than sites that were predicted to be ordered and to have secondary structure. Other important evolutionary determinants of the rate at which disordered regions evolve are synonymous constraint elements (Macossay-Castillo et al 2014) and gene age, as evolutionarily young proteins tend to be enriched in disordered regions (Wilson et al 2017).…”
mentioning
confidence: 99%
“…The selective forces governing this process have been studied by examining the properties of orphan proteins. Intrinsic disorder, low complexity, subtelomeric location, high β -sheet preference as well as other features have been associated with orphan proteins [16, 17]. It has also been proposed that with age proteins (i) accumulate interactions, (ii) become more often essential and (iii) obtain lower β -strand content and higher stability [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has later been shown that some of 14 these proteins are not de novo created but rather assigned as orphans as a result of 15 limited phylogenetic coverage in earlier studies [9]. 16 Today supported by the vast amount of complete genome sequences available and 17 improved search methods [10], many of the initially identified orphans have been shown 18 to have distant homologs in other genomes. Still, at least in yeast, a large set of genes 19 appears to have been created through recent de novo formation [11,12].…”
mentioning
confidence: 99%
“…The selective forces governing this 30 process have been studied by examining the properties of orphan proteins. Intrinsic 31 disorder, low complexity, subtelomeric location, high β-sheet preference as well as other 32 features have been associated with orphan proteins [16,17]. It has also been proposed 33 that with age proteins (i) accumulate interactions, (ii) become more often essential and 34 (iii) obtain lower β-strand content and higher stability [18].…”
mentioning
confidence: 99%